Probing the reactivity of the zinc and cadmium ions bound to rabbit liver metallothioneins with EDTA. - Nicholson,JK; Sadler,PJ; Vasák,M (Experientia Suppl, 1987)
Reactions of native and reconstituted rabbit liver metallothioneins (MT's) with excess EDTA at pH 7 were studied by 1H NMR, electronic absorption and atomic absorption spectroscopy. There was a reasonable agreement between the amounts of Zn2+ and Cd2+ removed as determined by the various methods. Specific structural changes accompanying metal removal were observable by NMR. Most of the Zn2+ in Zn7-MT, reacted rapidly with EDTA. One to two g-ions of Zn2+ in native Cd,Zn-MT's were labile, but none of the Cd2+ was extracted rapidly by EDTA. The cadmium protein Cd7-MT1, reconstituted via the low pH-apothionein method, appeared to contain EDTA-reactive Cd2+ bound in a different manner to either Zn2+ or Cd2+ in the native protein.